El proyecto arquitectónico: algunas consideraciones epistemológicas sobre el conocimiento proyectual (2010)
The considerations on the cognitive relationship among the fellow that projects and the projected object should leave of settling down with clarity the characteristics of this relationship, as a constant process of movement among these. A Movement that goes from the images to the concepts and vice-versa in a construction as intellectual as corporal of the subject and the deepest visibility that acquires the projected object